Impact of climate change on allergic diseases in Germany - Karl-Christian Bergmann; Randolf Brehler; Christina Endler; Conny Höflich; Sabine Kespohl; Maria Plaza; Monika Raulf; Marie Standl; Roma Thamm; Claudia Traidl-Hoffmann; Barbora Werchan (Journal of Health Monitoring, 2023)
Background: Allergic diseases, especially inhalation allergies, have reached epidemic levels and environmental factors play an important role in their development. Climate change influences the occurrence, frequency, and severity of allergic diseases. Methods: The contents of this article were selected by the authors and developed section by section according to their expertise and the current state of knowledge. The sections were then discussed and agreed upon amongst all authors. Results: The article highlights direct and indirect effects of climate change on allergies. It goes into detail about the connections between climate change and (new) pollen allergens as well as (new) occupational inhalation allergens, explains the effects of climate change on the clinical picture of atopic dermatitis, discusses the connections between air pollutants and allergies, and provides information about the phenomenon of thunderstorm asthma. Conclusions: There is a need for action in the field of pollen and fungal spore monitoring, allergy and sensitisation monitoring, urban planning from an allergological perspective, and changes in the working environment, among others.